“Epic-Genetics”: An exploration of preservice helping professionals’ (mis)understanding of epigenetic influences on human development (Teaching and Learning Inquiry, 2020)
Mental health researchers emphasize the importance of practitioner understanding of biology-environment interplay. Accordingly, our goal of the study described in this article was to understand students’ preconceptions and misconceptions about biological and environmental influences on development through investigating their conceptions of epigenetics. Using a short-term longitudinal design, we explored preservice helping professionals’ conceptions and misconceptions pertaining to epigenetics within the framework of a graduate level human development course. Baseline knowledge about epigenetics was low. Students developed multiple misconceptions about epigenetics and how the phenomenon relates to biological and environmental influences on human development. Students reported feeling highly efficacious for detecting and resolving misconceptions related to biology-environment interactions but varied in their perceptions of interest for learning about the content. Findings support the use of open-ended questions to detect misconceptions about epigenetics and are discussed in light of how to teach students about this phenomenon. Overall, this research speaks to the importance of understanding the misconceptions students believe and instructional strategies that may assist in correcting them.